Optimizing menarche readiness through video and leaflet health education interventions among primary school girls - Siregar, Erin Padilla; Manjorang, Novita Andriani Br; Artiani, Litri; Sembiring, Noviani (Jurnal Kesmas Prima Indonesia, 2025)
The counseling process requires engaging media to effectively enhance understanding and promote behavioral change within the target population. This study aimed to evaluate the impact of health counseling delivered through video and leaflet media on adolescents’ readiness to face menarche. A quasi-experimental design with a nonequivalent control group was employed. The study population consisted of students in grades 4 to 6 at SDN 101816, totaling 136 individuals. From this population, 60 respondents were selected and divided equally into two groups: one group (n = 30) received counseling via video media, while the other group (n = 30) received counseling through leaflets. Results indicated that adolescents' readiness to face menarche increased following health counseling with video media, with mean scores rising from 26.47 pre-intervention to 31.20 post-intervention, representing an improvement of 4.73 points. Statistical analysis confirmed a significant effect of video-based counseling on readiness (p < 0.001). Similarly, counseling using leaflet media resulted in an increase in readiness, with mean scores improving from 24.73 before intervention to 27.10 after, an increase of 2.34 points, also statistically significant (p < 0.001). Furthermore, comparison between the two groups revealed a significant difference in the effectiveness of video versus leaflet counseling approaches, favoring video media (p = 0.002). These findings suggest that health workers should prioritize the use of engaging media, such as videos, in health promotion efforts aimed at preparing adolescents for menarche.